Critical Synthesis Package: Scale of Emotional Arousability (SEA) - Rebecca D. Blanchard (Association of American Medical Colleges, 2013)
Abstract This Critical Synthesis Package contains: (1) a Critical Analysis of psychometric properties and application to health sciences research of the Scale of Emotional Arousability (SEA), and (2) a copy of the SEA developed by Valerie Braithwaite, PhD. The SEA is a self-administered scale of emotionality. Because it was based on other solidly constructed measures, the SEA has some precedent in the personality literature as a valid, short, self-administered measure of neuroticism, or emotional over-responsiveness. The 15-items of the SEA support four subscales; General Emotionality (6 items), Anger (3 items), Timidity (3 items), and Lack of control (3 items). Nine of the 15 items are reverse coded. Respondents answer items on a 5-point Likert scale with response options ranging from (1) "very unlike me" to (5) "very like me," and the neutral response is (3) "I am not sure." Scores can range from 15-75, where higher scores indicate a higher level of emotional arousal. Although the primary target population for the SEA was not specifically identified, development and validation studies focus on adults (age > 18) in the general population. While the SEA has been used for research on patients in public health research, it has only scratched the surface of health sciences educational research. Support for the SEA is strong but will need to be more detailed before its application to health sciences education research is evidentiary.